2014
DOI: 10.1111/his.12405
|View full text |Cite
|
Sign up to set email alerts
|

Utility of PAX8 mouse monoclonal antibody in the diagnosis of thyroid, thymic, pleural and lung tumours: a comparison with polyclonal PAX8 antibody

Abstract: Monoclonal PAX8 antibody showed high specificity to thyroid tumours and was superior to the polyclonal antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 18 publications
3
35
0
Order By: Relevance
“…Although the result of staining for PAX8 can be positive for thymic carcinomas when a polyclonal antibody is used, this likely results from cross-reactivity to another PAX gene product, which is not reproduced when a monoclonal antibody is used. 169 More than IHC staining, clinical and radiologic correlation is important to confirm whether a tumor is arising in the lung or in the thymus.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…Although the result of staining for PAX8 can be positive for thymic carcinomas when a polyclonal antibody is used, this likely results from cross-reactivity to another PAX gene product, which is not reproduced when a monoclonal antibody is used. 169 More than IHC staining, clinical and radiologic correlation is important to confirm whether a tumor is arising in the lung or in the thymus.…”
Section: Squamous Cell Carcinomamentioning
confidence: 99%
“…In fact, using more specific monoclonal anti-PAX-8 antibodies, it has been demonstrated unequivocally that PAX-8 is not expressed in thymic tumors or lymphomas. [10][11][12] The lesson of this unfortunate ''mischaracterization'' of PAX-8 by using antibodies of inferior specificity is that it is quite important for the pathologist performing immunohistochemistry to have reasonable certainty about the specificity of the antibodies being employed in the laboratory. In the case of the cross-reacting PAX-8 antibodies, overreliance on the information provided by the vendor was partly responsible.…”
Section: Independent Organizationsmentioning
confidence: 99%
“…Some studies have reported PAX8 positivity in RMC, with polyclonal or unknown antibodies.9.13,16 It is necessary to know the differences in PAX8 antibody specificities. Polyclonal PAX8 antibody cross‐reacts with some of the other members of the PAX family . We have already evaluated the utility of a PAX8 monoclonal antibody .…”
Section: Discussionmentioning
confidence: 99%